Teacher labor markets, school vouchers, and student cognitive achievement: Evidence from Chile - Michela M. Tincani (Quantitative Economics, 2021)
I use administrative and survey data from Chile and a structural model to evaluate teacher policies in a market-based school system. The model accommodates equilibrium effects on parental sorting across school sectors (public or private), on the self-selection of individuals into teaching and across school sectors, and on teacher wages in private schools. I use the estimated model to simulate a reform that is planned to be implemented in Chile in 2023. Tying public school teacher wages to teacher skills and introducing minimum competency requirements for teaching is predicted to increase student test scores by 0.30 standard deviations and decrease the achievement gap between the poorest and richest 25% of students by a third. These impacts are ten times as large as the impact of a flat wage increase in public schools, and over twice as large as the impact of only introducing minimum competency requirements. The key driver of policy outcomes is an improvement in the pool of teachers, amplified by equilibrium effects on teacher wages in private schools. The equilibrium effects are large, accounting for 70% of estimated policy impacts.
Keywords: I24; J24; J31; J38; 330; achievement gaps; equilibrium effects; merit pay; parental sorting; rigid pay; teacher entry; Teacher labor markets; teacher sorting